A Novel Forkhead Box L2 Missense Mutation, c.1068G>C, in a Chinese Family With Blepharophimosis/Ptosis/ Epicanthus Inversus Syndrome. Issue 3 (9th May 2022) - Wang, Shaoyun; Ge, Shengfang; Zhuang, Ai
Abstract : Abstract: The aim of the study was to report a novel forkhead box L2 (FOXL2) missense mutation in a Chinese blepharophimosis/ ptosis/epicanthus inversus syndrome family. Three generations of the Chinese family with blepharophimosis/ptosis/epicanthus inversus syndrome were enrolled in this study. Blood samples from patients of this family were collected and then analyzed by whole-exome sequencing. Confocal microscopy was performed to detect the subcellular location of FOXL2. Transactivation studies were performed and verified with real time polymerase chain reaction. A novel mutation (c.1068G>C) located in the downstream of deoxyribonucleic acid-binding forkhead domain was identified. Confocal photos showed the novel mutation did not disturb FOXL2 function, and the mutant protein could still transactivate steroidogenic acute regulatory protein, a key regulator of primary ovarian failure (POF). Our study revealed a novel missense mutation (c.1068G>C) and expanded the spectrum of FOXL2 gene mutations.